Kinerja Pembangkit Listrik Tenaga Uap (PLTU) Berdasarkan Pemanfaatan Limbah Padat Kelapa Sawit Pada Pabrik PT. Rama Jaya Pramukti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The other processed product of palm oil mills (POM) is Palm Biomass Solid waste. This waste is massive produced and capable to be used as the energy source of electrical power. This research analizes the convertion of biomass waste as the fuel fired steam power plant in POM owned by PT. Ramajaya Pramukti located at Kampar, Riau Province. This POM has production capacity of 60 tons / hour. The type of data used in this analysis is secondary data which includes data on fresh fruit bunches (FFB) as well as waste produced by the POM. In January 2017, the POM process 20.722,799 tons of FFB and produce 1.191,561 tons of shells and 2.590,349 tons of fiber. The lowest process of FFB in 2017 occurred in June at 12.363,807 tons wich produses 710,918 tons of shells and 1.545,475 tons of fiber. The results of this research shows that calculation of the potential convertion of palm biomass by PT.Ramajaya Pramukti that can be used as energy for steam power plant to generate electrical power is 23.09 MWh in January 2017 and 12.004 MWh in June 2017. Key words: PLTU, Biomass, Electricity Palm Oil Mill